BIOINFORMATICS STUDY: PEPTIDE-BASED BIORECEPTOR IN SILICO DESIGN FOR CARDIAC TROPONIN I (CTNI) DETECTION IN MYOCARDIAL INFARCTION - Rachel Damairetha, Filasta
Cardiovascular disease has reached a mortality rate of 470,000 patients each year. Myocardial infarction accounts for 49.2% of these deaths. Myocardial infarction is a case of death of the heart muscle (myocardium) due to interrupted or stopped blood supply to the myocardium. Myocardial infarction requires rapid treatment because this condition can cause irreversible damage to heart muscle tissue. The cTnI molecule is an important target protein in the diagnosis of myocardial infarction. Assessment of its levels in human blood serum is an important step to make the right diagnosis. Thus, in this final project, a peptide-based bioreceptor design was developed to develop a rapid and effective detection method for cTnI. For that, the process starts from the selection of peptide sequences in the binding site of the crystal structure of the cTnI/protein complex available in the Protein Data Bank (PDB) to mimic the recognition mechanism. Then, mutations were made to the peptide to increase its stability and affinity for cTnI. Next, molecular docking was performed for the selection of mutated peptides that have the most favorable binding affinity to cTnI. A total of five best mutated peptides were observed for their movement dynamics towards cTnI for 25 ns in aqueous solvent through molecular dynamics simulation to determine the binding stability of the peptide complex towards cTnI. Several parameters such as RMSD, RMSF, radius of gyration, SASA, and number of hydrogen bonds were analyzed to select the candidate peptide as the best bioreceptor. The analysis results showed that the design peptide with the sequence "WQTIYNLWAEKFDLQEKFKQQKYEINVERNRINDN" showed the most favorable affinity and stability among other mutated peptide designs. The peptide had a change in binding affinity energy compared to before mutation (??G) of -4.6 kcal/mol and showed stability when interacting with the amino acid residues of cTnI. There are two amino acid peptides that were observed to interact constantly during the simulation time with cTnI, namely Gln2 and Lys19. In addition, the peptide has been tested to have high specificity towards cTnI than its major